Expressão gênica diferencial de laranja Pêra Rio (Citrus sinensis (L.) Osbeck) e Lima Ácida 'Galego' (Citrus aurantifolia Swingle) em resposta à infecção por Xanthomonas citri subsp. citri - Cavallini, Juliana da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The citrus agribusiness is very important to the Brazilian economy, but the increase of diseases in the last decade has caused great economic losses to the sector. The citrus canker, caused by the bacterium Xanthomonas citri subsp. citri (Xac), is a serious disease that attacks all citrus species economically important worldwide and there is not an effective method for its control. In this study, RNASeq was used to analyze the transcriptional profiles of two contrasting citrus genotypes regarding citrus canker susceptibility: sweet orange Pêra Rio (PR), moderately resistant, and Mexican lime ‘Galego´ (ML), highly susceptible. Gene expression were performed in a HiScanSQ System (Illumina) using total RNA isolated from leaves collected 24, 48 and 72 hours after Xac inoculation, with leaves inoculated with water been used as control. It were found 6,330, 3,478 and 6,795 differentially expressed genes (DGEs) in moderately resistant PR specie at 24, 48 and 72 hours after Xac inoculation, respectively, when compared with their controls. In the specie highly susceptible ML, it was identified 1,491, 5,621 and 2,145 DGEs after 24, 48 and 72 hours after Xac inoculation, respectively. Through the program Blast2GO, genes and metabolic pathways related to photosynthesis, cell signaling, hormone synthesis, transcription factors, among others, were found as involved in plant defense. This study revealed differences at the molecular level between PR and ML in response to citrus canker, showing that in the specie moderately resistant there is a greater activation of host defense mechanisms. Such informations can be used for the development of citrus plants with an adequate level of resistance to citrus canker

A citricultura é uma das principais atividades do agronegócio brasileiro, porém o aumento de doenças na última década tem causado grandes prejuízos a toda a cadeia produtiva. A doença cancro cítrico, causada pela bactéria Xanthomonas citri subsp. citri (Xac) é um grave problema para o setor, não havendo até o momento método eficaz para o seu controle. Nesse estudo, utilizando RNASeq, foram analisados os perfis transcricionais de dois genótipos hospedeiros contrastantes à doença: laranja doce Pêra-Rio (PR) moderadamente resistente, e Lima Ácida Galego (LG), altamente suscetível, 24, 48 e 72 horas após a infecção com Xac, no intuito de identificar genes das plantas envolvidos na interação patógeno-hospedeiro. Foram encontrados 6.330, 3.478 e 6.795 genes diferencialmente expressos (GDEs) na espécie moderadamente resistente PR, 24, 48 e 72 horas após a inoculação com Xac, respectivamente, quando comparados com seus controles. Na espécie altamente suscetível Limão Galego foram identificados 1.491, 5.621 e 2.145 GDEs após 24, 48 e 72 horas da inoculação com Xac, respectivamente. Através do programa Blast2GO, genes e vias metabólicas de fotossíntese, sinalização celular, síntese hormonais, fatores de transcrição, entre outros, foram encontrados. Esse estudo revelou diferenças associadas à resistência e desenvolvimento a nível molecular em PR e LG em resposta ao cancro cítrico, demonstrando que na espécie moderadamente resistente há uma maior ativação dos mecanismos de defesa. Tais estudos podem ser utilizados para o desenvolvimento de plantas de citros com adequado nível de resistência ao cancro cítrico
Keywords: Laranja - Doenças e pragas; Cancro cítrico; Acido ribonucleico; Xanthomonas; Bacterias fitopatogenicas; Expressão gênica; Orange